2011
DOI: 10.3109/02652048.2011.635426
|View full text |Cite
|
Sign up to set email alerts
|

Salmon calcitonin-loaded Eudragit® and Eudragit®-PLGA nanoparticles:in vitroandin vivoevaluation

Abstract: The main objective of this study was to prepare salmon calcitonin (sCT)-loaded Eudragit®RSPO, Eudragit®L100 and Eudragit®-poly(lactic-co-glycolic acid) blend nanoparticles for in vitro and in vivo evaluation as an oral drug delivery system. The prepared nanoparticles ranged in size from 179.7 to 308.9 nm with a polydispersity index between 0.051 and 2.75, and had surface charges ~ -11 to +6 mV. Efficient sCT encapsulation and release was observed with all the nanoparticle formulations. The polymer type was an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Uptake and transport studies on Caco-2 cells confirmed these results and showed that binding and transcellular transport of LMWH was higher for RS and RS/PLGA NPs than for PLGA NPs. Cetin et al (2010Cetin et al ( , 2011Cetin et al ( , 2012 [49][50][51] have developed PLGA NPs coated with several Eudragit ® polymers or PLGA-Eudragit ® blends to control the release profiles of small therapeutic molecules such as sodium diclofenac or metformin hydrochloride while for big proteins such as salmon calcitonin (sCT). These blends can increase oral bioavailability.…”
Section: Methacrylates (Eudragit ® )mentioning
confidence: 99%
“…Uptake and transport studies on Caco-2 cells confirmed these results and showed that binding and transcellular transport of LMWH was higher for RS and RS/PLGA NPs than for PLGA NPs. Cetin et al (2010Cetin et al ( , 2011Cetin et al ( , 2012 [49][50][51] have developed PLGA NPs coated with several Eudragit ® polymers or PLGA-Eudragit ® blends to control the release profiles of small therapeutic molecules such as sodium diclofenac or metformin hydrochloride while for big proteins such as salmon calcitonin (sCT). These blends can increase oral bioavailability.…”
Section: Methacrylates (Eudragit ® )mentioning
confidence: 99%
“…Salmon calcitonin is a peptide that causes a decrease in blood calcium levels and is used for the treatment of bone diseases such as osteoporosis [116]. When encapsulated in Eudragit®-PLGA NPs, it was able to be administered orally to rats and achieve a greater decline in blood calcium levels for 24 hrs compared with subcutaneous injections of free salmon calcitonin [117]. Finally, cyclosporine is a potent immunosuppressive agent used for the prevention of graft rejection [118].…”
Section: Applicationsmentioning
confidence: 99%
“…Therefore, it is important to 17 design feasible and effective peptide ligand modified SLNs to improve the oral 18 bioavailability of protein drugs and evaluating the influence of mucus. 19 Recently, two categories of peptide ligands were applied: epithelium targeting 20 peptide and permeation enhancing peptide. A CSKSSDYQC (CSK) peptide was 21 found to be an effective ligand exhibiting high affinity with goblet cells on the 22 epithelium [4].…”
Section: Introductionmentioning
confidence: 99%